Comparative study on the performance of zta cutting tool with the addition of different particle size of mgo additive - Mudzaffar, Raqibah Najwa; Mohd Khairy, Hanani Hani; Mohd Zaki, Nur Khairunisa; Ahmad Azhar, Ahmad Zahirani; Manshor, Hanisah; Rejab, Nik Akmar; Mohd Ali, Afifah (Trans Tech Publications Ltd, 2020)
This paper investigated the performance of ZTA cutting tool with the addition of different particle size of MgO additive. Therefore, the objective of this research is to compare the effects of machining parameters on tool wears of ZTA cutting tools added with micro and nanoparticle of MgO. The experiments were conducted using BridgePort-Romi Powerpath CNC machine using a tool holder Sandvik Coromant (CoroTurn CCLNR 164D-4) to hold the cutting tools properly. The parameters are set up as cutting speeds used between range 354 to 472 m/min, feed rate from 0.1 to 0.5 mm/rev with a constant depth of cut of 0.2 mm. Three types of wear were analyzed which are flank wear, crater wear and tool chipping. Flank wear and crater wear images captured using measuring microscope (NIKON MM-400/L) and the crater wear areas are analyzed using MatLab programming software. Tool chipping is observed via SEM (JEOL JSM-5600). The experimental result shows that flank wear and crater wear increase when cutting speed and feed rate increase. ZMN cutting tool shows lower value of flank wear at 0.143 mm and 3.741 mm2 for crater wear than ZMM, 0.321 mm and 3.808 mm2 respectively. On the contrary, cutting speed did not affect the tool chipping severely as feed rate. Moreover, ZMN also shows that the tool breakage occurred severely than ZMM due to the high load on the tool nose.